Population dynamics, spatiotemporal distribution of the olive psyllid Euphyllura olivina, (Costa, 1839) (Hemiptera: Psyllidae) on the Chemlal variety in the Oasis of Boussaâda - Mourad Hamdani; Faiza Hoceini; Laid Benderradji; Mahdi Sellami (Journal of Oasis Agriculture and Sustainable Development, 2022)
The study conducted on the population dynamics of the olive psyllid Euphyllura olivina, (Costa, 1839), on the variety Chemlal in the oases of Boussaâda, during the first half of the year 2021, showed that the first numbers of the different biological stages of the insect are recorded in mid-March 2021, where all directions of the tree are infested while the northern and western directions are the most exposed to attacks of the pest.